CLINICAL ASPECTS OF PATIENTS WITH NON-REMOVABLE PROSTHESIS RESULTS OF ZRO2 COATED PROSTHESES - O.M. Yakovyn; Z.R. Ozhohan (Ukrainian Medical Stomatological Academy, 2017)
The clinical aspects of prosthetic patients with dentition defects of different types of orthopedic designs are reproduced in the article. The aim of our research is to improve the treatment of patients with orthopedic defects dentition using aesthetic fixed prosthetic appliances by improving their manufacturing stages and grounding of the proposed treatment methods. The objects of our study are patients who have orthopedic constructions made of dental alloys of non-precious (basic) metals. Groups include 100 patients of age 20-55 years, where existing orthopedic constructions are made of dental alloys of non-precious (basic) metals, as well as control group of patients for who orthopedic constructions based on zirconium dioxide is made. The first group includes patients with non-removable combined ceramic structures. The second group includes patients who have combined metal-made prosthetic dentures with a protective coating ZrO2. The third group - patients with non-removable prosthetic dentures made of zirconium dioxide. Patients of various groups held determination of the PMA index, Index Silness- Loe, Shyllyera -Pysaryeva test. The results of examination were noted before treatment, after 3, 6 and 12 months after beginning of treatment. Analysis PMA index before treatment for patients with the figure 1, 2 and 3 groups was respectively 24,2 ± 2,1 points, 22,1 ± 1,6 points and 20,7 ± 1,3 points. After 3 months rate decreased to 3,2 ± 0,4 points in group 1 to 2,1 ± 0,3 points in group 2, and to 1,9 ± 0,2 points in 3rd group. After 6 months index increased in group 1 to 7,2 ± 1,1 points, in group 2 to 2,3 ± 0,4 points, and in 3rd group - to 2,0 ± 0,2 points. After 12 months PMA index in group 1 was 8,5 ± 1,4 points, 2nd group - 2,6 ± 0,5 points, and 3rd group 2,2 ± 0,3 points. Index Silness- Loe before treatment was (1.88 + 0.2) points in group 1 (1.95 + 0.2) points in group 2, and 1.75 + 0.1 points in group 3. After 3 months of treatment, this data decreased to (0.55 + 0.1) points in group 1 to (0.42 + 0.1) points in group 2, and 0.38 + 0.1 points in 3 group. After 6 months figures were in group 1st (0.94 + 0.1) points, group 2nd patients were (0.62 + 0.1) points, while the figure was 3rd group (0.52 + 0.1) points. After 12 months data in group 1st patients increased to (1.5 + 0.1) points, in group 2nd figures were (0.65 + 0.1) points, while 3rd droup had the best value (0.54 + 0 1) points respectively. Shyllyera - Pisarev test before treatment was (2.08 + 0.1) points in group 1st patients, and (2.12 + 0.2) points in 2nd group. In group 3rd of patients this data was (2.1 + 0 2) points. After 3 months rate decreased to (0.47 + 0.1) points in group 1st patients to (0.43 + 0.1) points in 2nd patients, and was the best (0.38 + 0.1) points in patients with fixed prostheses on the basis of ZrO2. After 6 months of performance in all groups of patients increased slightly, but remained best in groups 2 and 3. After 12 months data in group 1st of patients were worse and were (0.81 + 0.2) points; in group 2nd of patients, the rate was the best and was (0.49 + 0.1) points, and in 3rd group (0.45 + 0.1) points, respectively.  Thus, analyzing the results of the research can be argued that in patients of group 1st after treatment was improved clinically, and periodontal status in chronological dynamics remained satisfactory. In patients of group 2nd for who orthopedic structures made of CСA and NCA with bioinert coating of ZrO2 were offered, in their indicators of periodontal tissues were close to data observed in patients within 3rd group with metal structures. Patients of 2nd and 3rd groups satisfied patients in terms of aesthetic and functional requirements. Shade, smoothness, integrity structures were remained unchanged. For 10 percent of patients studied in groups 2, 3 changes in marginal periodontal condition were observed, characterized by flushing and bleeding. In chronological dynamics unlike patients of group 1st patients in 2nd and 3rd group took place to improve the average indexes PMA, Silness- Loe, Schiller-Pisarev test.